Lilo & Stitch (New York : Scholastic Inc., 2002)
When a lonely little Hawaiian girl named Lilo makes a wish on a falling star, she doesn't realize the falling star is actually a spaceship being piloted by an out-of-this-world alien named Stitch, in a fictionalization of the Disney animated film.